2021
DOI: 10.3389/fcell.2021.706623
|View full text |Cite
|
Sign up to set email alerts
|

Hippo-Yap Pathway Orchestrates Neural Crest Ontogenesis

Abstract: Neural crest (NC) cells are a migratory stem cell population in vertebrate embryogenesis that can give rise to multiple cell types, including osteoblasts, chondrocytes, smooth muscle cells, neurons, glia, and melanocytes, greatly contributing to the development of different tissues and organs. Defects in NC development are implicated in many human diseases, such as numerous syndromes, craniofacial aberration and congenital heart defects. Research on NC development has gained intense interest and made significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…addition, NCC-derived eMSC osteogenesis in vivo is more complex than that of NCCs in vitro and is regulated by an intricate signaling network (52). We also cannot exclude the possibility that Yap and Taz only function in a certain group of NCC-derived eMSCs instead of all NCCs, which is worthy of further investigation in the future.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…addition, NCC-derived eMSC osteogenesis in vivo is more complex than that of NCCs in vitro and is regulated by an intricate signaling network (52). We also cannot exclude the possibility that Yap and Taz only function in a certain group of NCC-derived eMSCs instead of all NCCs, which is worthy of further investigation in the future.…”
Section: Discussionmentioning
confidence: 91%
“…An important limitation of our in vivo model is that the mutant embryos retain a single functional copy of Yap , which may be sufficient to support some of the redundant roles of Yap and Taz in vivo or in a subset of skull structures. In addition, NCC-derived eMSC osteogenesis in vivo is more complex than that of NCCs in vitro and is regulated by an intricate signaling network ( 52 ). We also cannot exclude the possibility that Yap and Taz only function in a certain group of NCC-derived eMSCs instead of all NCCs, which is worthy of further investigation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other pathways have been suggested to play a role in neural crest development, such as retinoic acid signaling [ 40 , 41 ] and the Hippo/YAP pathway. For example, recent findings suggest that Hippo/YAP promotes neural crest fate and migration, as well as fate specification of neural crest cells (reviewed by Zhao et al, 2021 [ 42 ]): YAP activation could benefit the EMT and migration of neural crest cells, and studies have suggested the crosstalk of YAP signaling with that of BMP and Wnt [ 43 ], retinoic acid [ 44 ], and Notch [ 45 ] during neural crest development.…”
Section: In Vivo Development Of Schwann Cellsmentioning
confidence: 99%
“…One of the central regulators is the Hippo pathway, which plays a pivotal role in heart failure (Wang et al, 2018 ). The Hippo pathway targets not only mitochondria but also other organelles and pathways (Zhao et al, 2021 ). Mammalian sterile 20-like kinase 1 (MST1) is a crucial component in the Hippo pathway (Zhao et al, 2021 ).…”
mentioning
confidence: 99%
“…The Hippo pathway targets not only mitochondria but also other organelles and pathways (Zhao et al, 2021 ). Mammalian sterile 20-like kinase 1 (MST1) is a crucial component in the Hippo pathway (Zhao et al, 2021 ). Feng et al observed that knockout of Mst1 inhibited mitochondrial division and reduced left ventricular remodeling in diabetic cardiomyopathy, thereby highlighting the critical role of the Hippo pathway in the regulation of mitochondria and CVDs.…”
mentioning
confidence: 99%